Comparative study of Ultrasonography with Fine Needle Aspiration Cytology in the diagnosis of causes of Obstructive Jaundice - Pandit, Swoyam Prakash; Pandit, S; Pandit, S (Nepalese Journal of Radiology, 2017)
Introduction: Surgical jaundice or obstructive jaundice is one of the common causes of jaundice. It is important cause of morbidity and mortality in an adult commonest at 40-60 years of age and the incidence is increasing day by day. The purpose of this study was to use easily available ultrasonography in the diagnosis of causes of obstructive jaundice and to determine its effectiveness by comparing with Fine Needle Aspiration Cytology (FNAC). Methods: Non- randomized, prospective study of 35 cases with clinical features of jaundice and altered bio-chemical test was conducted over a period of one year. The ultrasound findings were compared with FNAC to characterize the cause of obstruction. Result: Out of 35 cases, 24 cases were subjected to USG guided FNAC for suspicion of malignancy for confirmation. USG showed 18(51%) had benign causes, 11(31%) malignant and 6(17%) were indeterminate. FNAC result showed 13 (54%) were malignant. Over all accuracy of USG in determination of cause of obstruction is high as 83%. The efficacy of the USG is acceptable when compared with histopathology (P value is 0.6816). Conclusion: Ultrasonography correctly predicted the causes of obstruction whereas in malignant cases, when combined with other modality, accuracy of diagnosis can be increased. NJR VOL 4 No. 2 ISSUE 7 July-December, 2014, page: 1-5